KARAKTERISTIK SOSIAL EKONOMI PEDAGANG SEKTOR INFORMAL DI PASAR BERSEHATI KOTA MANADO - Suwito La Uto; Nordy F. L. Waney; Agnes E. Loho (AGRI-SOSIOEKONOMI, 2018)
This study aims to examine the social economic characteristic of informal sector traders. The research took place from October to December 2017 at Market of Bersehati Manado, Calaca Urban Village, Wenang Sub-district, Manado City. Collection method in this research is primary and secondary data. Sampling method in this research is done by Accidental Sampling. The number of samples were taken in this study were 30 respondents consists of 15 respondents of vegetable sellers and 15 respondents of spice merchants. The research results showed that vegetable sellers and spice merchants who working in the informal sector, most of them have a simple background, both traders are able to meet the needs of everyday families with their own capital and basic capital of trust. They earned an average income of vegetable sellers IDR 63,868 and spice merchant IDR 276,950.